2003
DOI: 10.1677/joe.0.1780127
|View full text |Cite
|
Sign up to set email alerts
|

Expression of 11beta-hydroxysteroid dehydrogenase (11betaHSD) proteins in luteinizing human granulosa-lutein cells

Abstract: In a range of tissues, cortisol is inter-converted with cortisone by 11 -hydroxysteroid dehydrogenase (11 HSD). To date, two isoforms of 11 HSD have been cloned. Previous studies have shown that human granulosa cells express type 2 11 HSD mRNA during the follicular phase of the ovarian cycle, switching to type 1 11 HSD mRNA expression as luteinization occurs. However, it is not known whether protein expression, and 11 HSD enzyme activities reflect this reported pattern of mRNA expression. Hence, the aims of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…The 11bHSD enzymes control cortisol metabolism by their type 1 (that tends to generate cortisol) and type 2 (that tends to inactivate cortisol) isoforms. Numerous studies have shown clear evidence that there is a switch in 11bHSD isoforms associated with the follicularluteal transition (Michael et al 1997, Tetsuka et al 1997, Yong et al 2000, Thurston et al 2003. We have confirmed this switch in women at a protein level and localised expression to the granulosa/granulosa-lutein cells of the ovary.…”
Section: Cells (G) Of An Antral (A) Follicle (A-c) and The Granulosa-supporting
confidence: 78%
See 1 more Smart Citation
“…The 11bHSD enzymes control cortisol metabolism by their type 1 (that tends to generate cortisol) and type 2 (that tends to inactivate cortisol) isoforms. Numerous studies have shown clear evidence that there is a switch in 11bHSD isoforms associated with the follicularluteal transition (Michael et al 1997, Tetsuka et al 1997, Yong et al 2000, Thurston et al 2003. We have confirmed this switch in women at a protein level and localised expression to the granulosa/granulosa-lutein cells of the ovary.…”
Section: Cells (G) Of An Antral (A) Follicle (A-c) and The Granulosa-supporting
confidence: 78%
“…The HSD11B enzyme isoforms change during luteinisation (Michael et al 1997, Tetsuka et al 1997, Yong et al 2000, Thurston et al 2003. The predominant isoform in follicular granulosa cells is HSD11B2 (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…In contrast, bovine and human granulosa cells were found to express 11b-HSD1, but not 11b-HSD2 (Tetsuka et al 2003;Chandras et al 2007). Other studies showed that human granulosa cells expressed 11b-HSD2 message during the follicular phase, and upon stimulation, ceased to express 11b-HSD2 and began to express 11b-HSD1 (Thurston et al 2003a). As in our rats, both HSD enzymes were reported in the bovine corpora lutea, with 11b-HSD2 expression increasing in comparison to that of 11b-HSD1 as the corpora lutea matured (Tetsuka et al 2003).…”
Section: Discussionsupporting
confidence: 75%
“…In our present studies, IHC did not detect H6PDH in rat granulosa cells, which would further decrease the availability of NADPH. The resulting decrease in local cortisol concentrations was thought to be important in the late follicular phase (Thurston et al 2003a(Thurston et al ,2007). An endogenous inhibitor of 11b-HSD reductase activity produced by granulosalutein cells has been proposed (Thurston et al 2003b), and inappropriate production of this inhibitor has been postulated to be the cause of infertility in some women (Michael et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of steroidogenic enzyme mRNAs was also determined by RT-PCR. Additionally, western blot analysis for a steroid metabolizing enzyme, 11b-hydroxysteroid dehydrogenase (11b-HSD; Thurton et al 2003) as a marker of steroidogenic cells, was performed. The concentrations of P 4 in the conditioned medium of the preparation T SAKURAI and others .…”
Section: Isolation Culture and Characterization Of Luteal Ecsmentioning
confidence: 99%